2009 Florida Dairy Farm Situation - Albert De Vries; Russ Giesy (EDIS)
AN215, a 3-page illustrated fact sheet by Albert De Vries and Russ Giesy, presents an analysis of the depressed profitability expected for Florida dairy production in 2009. Includes references. Published by the UF Department of Animal Sciences, March 2009.